Сэндвич-панель - Гайслер Е. В. Евгений Владимирович; Волокитин Г. Г. Геннадий Георгиевич; Скрипникова Н. К. Нелли Карповна; Аниканова Л. А. Любовь Александровна; Лысак И. А. Илья Александрович
опубл. 27.06.07